2017
DOI: 10.1111/cup.13074
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐Barr virus positive diffuse large B‐cell lymphoma presenting with vaginal sloughing and ulcerated skin nodule

Abstract: Malignant lymphomas presenting in the female genital tract are extremely rare. We report a case of Epstein-Barr virus associated diffuse large B-cell lymphoma of the genital tract and skin in a 60-year-old woman on long-term azathioprine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A cohort study among people with inflammatory bowel disease found that use of thiopurines, which include azathioprine, resulted in a multivariate-adjusted hazard ratio of greater than 5 for development of lymphoproliferative disorders [ 19 ]. Case reports have been published of diffuse large B-cell lymphoma (DLBCL) developing in the setting of azathioprine use within the gastrointestinal tract [ 20 , 21 ], the genitourinary organs [ 22 , 23 ], the central nervous system [ 24 ], and the skin [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…A cohort study among people with inflammatory bowel disease found that use of thiopurines, which include azathioprine, resulted in a multivariate-adjusted hazard ratio of greater than 5 for development of lymphoproliferative disorders [ 19 ]. Case reports have been published of diffuse large B-cell lymphoma (DLBCL) developing in the setting of azathioprine use within the gastrointestinal tract [ 20 , 21 ], the genitourinary organs [ 22 , 23 ], the central nervous system [ 24 ], and the skin [ 25 ].…”
Section: Introductionmentioning
confidence: 99%